Pathologic evaluation of response to neoadjuvant therapy drives treatment changes and improves long‐term outcomes for breast cancer patients. Issue 6 (29th May 2020) - Bossuyt, Veerle; Spring, Laura
Abstract: Systemic therapy for breast cancer may be given before (neoadjuvant) or after (adjuvant) surgery. When neoadjuvant systemic therapy is given, response to treatment can be evaluated. However, some prognostic information (for example, pathologic tumor size pretreatment) is then lost and pathologic evaluation of breast specimens after neoadjuvant therapy is more difficult. Pathologic complete response (pCR), defined as no invasive disease in the breast (ypT0/is or ypT0) and no disease in all sampled lymph nodes (ypN0), identifies patients with a lower risk of recurrence or death compared to those with residual disease. Multidisciplinary collaboration, marking of the tumor site and any lymph node involvement pretreatment, and access to specimen imaging to facilitate correlation of gross and microscopic findings are critical for accurate determination of pCR. For HER2‐positive and triple negative tumors requiring systemic therapy, giving the treatment before surgery identifies a high‐risk group of patients that can receive additional adjuvant therapy after surgery if a pCR is not achieved. Recent clinical trials have demonstrated that this approach reduced recurrence risk. More than ever, pathologic evaluation of response to neoadjuvant systemic therapy directs treatment received after surgery. Using a single standardized protocol for sampling of the post‐neoadjuvant surgical specimen allows pathologists to ensure accurate determination of pCR or residual disease and quantify residual disease. Residual cancer burden (RCB) and AJCC stage provide complementary quantitative information about residual disease and prognosis.